The Effect of Training Method and Arm Length on Spike Back Attack Ability in Junior Athletes of Bina Taruna Semarang Volleyball Club - Ahmad Fahmi Hidayatullah; Nasuka Nasuka; Agung Wahyudi (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2022)
The purpose of this study was to analyze the difference in the effect of hanging ball training methods and self-throwing ball training methods, above-average arm length and below-average arm length, and whether there is an interaction between training methods and arm length on the ability of spike back attacks in junior volleyball athletes. This study used an experimental method with a 2x2 factorial design. The population in this study was 25 junior athletes of Bina Taruna Semarang volleyball club. The sample of this study was 20 athletes taken by purposive sampling technique. The instruments in this study used an anthropometer and a Robert E Laveaga spike test. Data analysis in this study used the ANOVA test (two-way) followed by the Tukey test with a significant level of α = 0.05. The results of the study are as follows: (1) There is a difference in the effect between the training method (hanging ball and self-throwing ball) on the ability of spike back attack, as evidenced by the calculated F value of 9.308 with a significance of 0.008. (2) There is a difference in arm length (above average and below average) on the ability to spike back attack, as evidenced by the calculated F value of 6.231 with a significance of 0.024. (3) There is an interaction between the training method (hanging ball and self-throwing ball) and arm length (above average and below average) on the ability of spike back attack, as evidenced by the calculated F value of 6.231 with a significance of 0.024.